Development of Augmented Reality-Based Learning Media on Atomic Absorption Spectrophotometer (AAS) Material - Nur Fauzi’ah Nasution; Ida Farida; Yulia Sukmawardani; Silmi Rahma Amelia (International Journal of Learning Media on Natural Science (IJLENS), 2025)
Atomic absorption spectrophotometer (AAS) instruments are not always found in universities or high schools, due to the high and complex maintenance and operation costs of these instruments. To overcome this, innovative learning media are needed that can visualize and facilitate understanding of concepts in AAS material. This study aims to describe the design of the learning media display, analyze the results of validation tests, and analyze the results of the feasibility test. The research method used is Design Based Research (DBR) with the ADDIE model approach. The results of the study are in the form of a learning media display design consisting of a home page (cover), a main menu consisting of learning objectives, instructions for use, materials, AR scans, quizzes, and compiler profiles. The material page consists of images about phenomena in everyday life and videos about the working principles of AAS, sample preparation processes, simulations of AAS data measurement and analysis, and data interpretation in the form of images and articles. The AR scan page consists of a menu of AAS components. The results of the validation test obtained an average value of 0.83, this indicates that the augmented reality-based learning media on AAS material is categorized as valid with high interpretation. Meanwhile, the results of the feasibility test obtained an average percentage value of 92.16%, this shows that augmented reality-based learning media on AAS material is very suitable for use as learning media.